Implikasi Penerapan Metode Tutor Sebaya dalam Peningkatkan Hasil Belajar Fisika Siswa Di SMA Negeri 4 Cirebon - Yeni Nuriyani; Widodo Winarso (Universitas Sarjanawiyata Tamansiswa, 2021)
Classroom action research using peer tutoring methods to improve learning outcomes in physics subject circular motion. This study's subjects were students of class X MIPA 3 SMA Negeri 4 Cirebon Cirebon City, West Java Province, totaling 32 students. The data collection technique is done by testing and observation. The research process was carried out in two cycles, each cycle consisting of four stages, namely: (1) action planning, (2) action implementation, (3) observation and interpretation, and (4) analysis and reflection. Based on the research that has been done, it can be concluded that there is an increase in learning outcomes in physics subject of student circular motion through the use of the Peer Tutor method. Pre-cycle data with a class average of 60.94 with a percentage of 28.13% complete learning or 9 students out of 32 students. The first cycle increased to 72.19% or 17 students completed with an average student grade of 53.13%, but this score had not yet reached the KKM that had been agreed upon. The second cycle increased to 81.25% or 26 students completed with an average student score of 84.84. Thus, the peer tutor method's application can improve learning outcomes in the Physics subject of circular motion so that it is feasible to be applied in SMA Negeri 4 Cirebon.